Reaching out and reaching up - developing a low cost drug treatment system in Cambodia - Klein Axel; Saphonn Vonthanak; Reid Savanna (BMC, 2012)
Abstract Cambodia, confronted by the spread of drug misuse among young people, requested support from international agencies to develop a drug treatment programme in 2000. The initial plan developed by the United Nations Office on Drugs and Crime was to set up a number of conventional drug treatment centres in urban areas. During the planning phase, however, the project was redesigned as a community based outreach programme. Ten Community Counselling Teams have been formed and trained in pilot areas, and within the first year of operation 462 drug and alcohol users contacted. Comprising former drug users, family members affected by drug use and health care staff, they have drug scene credibility, local knowledge and connectivity, and a rudimentary level of medical competence. Crucially, they enjoy the support of village elders, who are involved in the planning and reporting stages. While the Community Counselling Teams with their basic training in addiction counselling are in no position as yet to either provide or refer clients to treatment, they can provide brief interventions, organise self help groups, and most importantly provide an alternative to law enforcement. By taking a development centred approach, with emphasis on community, empowerment and inclusion, it provides a constructive and inclusive alternative to medical approaches and the compulsory drug treatment centres. The paper is based on an evaluation involving interviews with a range of stakeholders and a review of project documents.